2004
DOI: 10.1176/appi.ajp.161.11.2132
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole Augmentation for Treatment-Resistant Depression

Abstract: TO THE EDITOR: Glutamate is implicated in the pathophysiology and treatment of mood disorders (1). The following case reports pertain to the use of riluzole, a putative antiglutamatergic agent indicated for the treatment of amyotrophic lateral sclerosis, as add-on therapy for treatment-resistant major depressive disorder. Ms. A wasa 42-year-old woman with a history of major depressive disorder. Despite pharmacotherapy strategies, including fluoxetine, fluoxetine augmented with lithium, and her current regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…Over the six-week trial, subjects received a mean riluzole dose of 95.0 ± 17.1 mg/day. .05] scores remained significant in separate analyses excluding two subjects who were previously described in a case report (Sanacora et al 2004).…”
Section: Resultsmentioning
confidence: 93%
“…Over the six-week trial, subjects received a mean riluzole dose of 95.0 ± 17.1 mg/day. .05] scores remained significant in separate analyses excluding two subjects who were previously described in a case report (Sanacora et al 2004).…”
Section: Resultsmentioning
confidence: 93%
“…14 A recent series of openlabelled studies and case reports demonstrated its efficacy. [15][16][17][18][19] Although the glutamatergic system may influence directly or indirectly the serotonergic and noradrenergic neurotransmission, there are only few data in the literature dealing with this interaction. NMDA receptor antagonists increase the serotonin levels in the brain.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…Case reports and open label studies suggest efficacy in the treatment of major depression, 11,12,112,113 bipolar depression, 114,115 anxiety, 12 and OCD. 12 Ongoing studies examining the effect on schizophrenia have also begun at our center (Zimolo, Z., Yale University, personal communication).…”
Section: 111mentioning
confidence: 99%